The Effect of Internal Communication and Teamwork on the Performance of the Student Organization Board at Ar-Raudlatul Hasanah Islamic Boarding School in Medan - Faisal, Harik Aziz; Hulu, M. Rizki Hanif; Jannah, Miftahul; Hamdan, Al-Hafizh Mubarak (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study aims to determine the effect of internal communication and team collaboration on the performance of the student organization board at Ar-Raudlatul Hasanah Islamic Boarding School in Medan. A descriptive quantitative research design was employed. The population comprised the active board members of the student organization at Ar-Raudlatul Hasanah. A purposive sampling technique was applied, yielding a total sample of 125 respondents. Data were collected through a structured questionnaire and analyzed using simple linear regression, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings reveal that internal communication does not have a statistically significant partial effect on the performance of the student organization board. In contrast, team collaboration exhibits a positive and significant partial influence on board performance. Furthermore, internal communication and team collaboration collectively have a positive and statistically significant simultaneous impact on the performance of the student organization board at Ar-Raudlatul Hasanah Islamic Boarding School, Medan.